Report on Phase 1 Planning Meeting of the Paddy Rice Production Component CCAC Agriculture Initiative - Sander, Björn Ole; Joven, B.P. (2014)
The goals of the Climate and Clean Air (CCAC) Agriculture Initiative are to disseminate best practices for minimizing emissions of short-lived climate pollutants (SLCPs) from agriculture while also enhancing food security and livelihoods and meeting cross-sectoral climate change objectives.